Leaf Anatomy Structure of Codiaeum variegatum (L.) Rumph. ex A. Juss Cultivars - Hayatul Fajri; Anisyah Yuniarti; Ari Sunandar; Wolly Candramila (Jurnal Penelitian Pendidikan IPA, 2024)
Codiaeum variegatum (L.) Rumph. ex a. Juss is a common ornamental plant with a high variation of leaves shape and colour. This study aimed to analyze the leaves’ anatomy and the phenetic relationship between eight cultivars of C. variegatum which were defined by the differences in leaf morphology. The paraffin method prepared the transversal section of leaves, and anatomical characters were converted into binary data to calculate the similarity coefficient which was analyzed by Numerical Taxonomy System (NTSYS) 2.1 version. Leaves of eight cultivars of C. variegatum are varied in the anatomical structure of the primary vein and lamina. The eight cultivars of C. variegatum were clustered into four. The variations were found in 19 primary vein and lamina anatomy characteristics and the similarity coefficient is up to 0.59 between all cultivars. It can be concluded that the combination of leaf anatomical structures and midrib anatomical characters have notable taxonomic implications for future research.